Regularization of lands of the remaining quilombos communities and the memory of traditions - Silva , Larissa Souza Lima da; Reis, Luciana Araújo dos (Seven Editora, 2023)
Symbolically represented, the land is considered a materialization of the tradition and culture of the quilombola communities. From this perspective, it is evident the need to analyze the legal aspects that comprise its regularization, since there is legislation that recognizes the right to definitive ownership of the territories to these populations. In this context, the relevance of the theme becomes understandable when it comes to the ineffectiveness of the rights of the remaining populations. The objective is to reflect on the social function that permeates the territories known as former quilombos, exteriorized in the preservation of memory; and to analyze how the social memory of these groups constitutes itself as an arsenal in the struggle for positive rights that lack practical effectiveness. This is a scientific production of a qualitative nature, elaborated from the inductive method and critical reflective investigation, with a corpus formed by legislation, legal and agricultural doctrine, and sociological contributions. Thus, the research points to the need to think about the land from a perspective superimposed on heritage issues, focusing on the identity of the group in its ancestry, formed by a set of symbologies incorporated into the physical space. Finally, it is considered that the preservation of the memory of tradition will only become possible when the fundamental rights and guarantees of this population group are fully achieved. DOI:https://doi.org/ 10.56238/devopinterscie-212